Numerasi Siswa SMP dalam Memecahkan Soal Setara AKM Konten Geometri dan Pengukuran Ditinjau dari Kecerdasan Majemuk - Novi Eka Nor Rosidah; Rooselyna Ekawati (Program Studi S1 Matematika UNESA, 2023)
This study aims to describe the numeracy of junior high school students in solving AKM geometry and measurement content questions in terms of multiple intelligences. The research method used is descriptive research method with a qualitative approach. The research subjects were three students selected by purposive sampling, each of whom had linguistic, logical-mathematical, and spatial intelligence. The research instruments are multiple intelligence identification tests, mathematical ability tests, AKM tests of geometry and measurement content, and interview guidelines. The results of the study show that subjects with linguistic intelligence through several processes namely (1) identifying and representing information in mathematical form using language representations and symbol representations, but the choice of words used is inappropriate; (2) design and implement strategies to obtain solving results in line with AKM problems, geometry and measurement content; and (3) interpret the results of the solution by making conclusions according to the context of the problem in the AKM problem geometry and measurement content. Subjects with logical-mathematical intelligence through several processes, namely (1) identifying information and representing it in mathematical form i.e. using language representations and symbol representations; (2) design and implement strategies to obtain the results of solving geometry and measurement AKM problems using mathematical concepts; and (3) interpret the results of the solution obtained by making conclusions according to the context of the problem on the AKM geometry and measurement. Subjects with spatial intelligence through several processes, namely (1) identifying information and representing it in mathematical form using representations of language, symbols, and images; (2) design and implement strategies to obtain solving results from geometry and measurement AKM problems using mathematical concepts; and (3) interpret the results of the solution obtained by making conclusions in accordance with the context of the problem in the in line with AKM problem, geometry content and measurement.